The determinants of derivative usage: a study of financial services in Malaysia / Farhana Jainal Ariffin - Jainal Ariffin, Farhana (Faculty of Business and Management, 2014)
This paper aims to analyses the relationship between determinants of derivative usage among financial services in Malaysia. The study used Multiple Linear Regression Model to determined significant relationship between dependent and independent variables, covering data for 14 companies with 5 years period which are from 2009 until 2013. The researcher used five independent variables that affect the derivative usage which are debt, investment growth, managerial ownership, liquidity and profitability. Debt consists of two proxy variables which are leverage and debt to equity, investment growth consists of proxy variables of capital expenditure and dividend payout ratio, managerial ownership with proxy variable of number of shareholding, liquidity with proxy variables of current ratio and quick ratio and profitability with proxy variables of return on assets and return on equity. The empirical results have found there is positively significant relationship between derivative usage and managerial ownership. The results of the study are valuable for both academic and investor.